Magnet Variation Produces 82.9 Volt Generator Output: Perubahan Magnet Menghasilkan Output Generator sebesar 82,9 Volt - Andika Tri Serviantyo Sukma Kusnadi; A’rasy Fahruddin (Indonesian Journal of Innovation Studies, 2026)
General Background The increasing demand for electrical energy requires alternative solutions to support power generation, especially in remote areas. Specific Background Permanent magnet generators provide a practical approach by converting mechanical energy into electrical energy without requiring external excitation. Knowledge Gap However, the influence of varying magnet quantities in modified generators from used equipment has not been clearly explored. Aims This study aims to design and test a generator from a used water pump with variations of 8, 10, and 12 neodymium magnets on the rotor. Results Experimental results show that the generator with 12 magnets produces the highest output, reaching 51.7 V at 1500 rpm, 68.0 V at 2000 rpm, and 82.9 V at 2500 rpm, while lower magnet variations produce significantly smaller voltages and currents. Novelty The study introduces a modification approach using a used water pump combined with varying magnet configurations to optimize electrical output. Implications The findings indicate that increasing the number of magnets significantly improves generator performance, offering a simple and low-cost solution for small-scale electricity generation in areas with limited access to conventional power sources. Keywords: Permanent Magnet Generator, Electrical Energy, Neodymium Magnet, Rotor Modification, Voltage Output Key Findings Highlights Highest output achieved at maximum rotation speed with largest magnet configuration Smaller configurations generate minimal electrical output under load Output characteristics differ significantly between load and no-load conditions